(untitled) (Orfeu, 2018)
We are pleased to announce the release of the special issue on the Psychology of Music of the ORFEU Journal (vol.3, no.1), edited by the guest editors Dr. Luciana Hamond (PPGMUS / UDESC) and Professor Graham Welch (UCL Institute of Education, UK).